The Founding of the Red Trade Union International : Proceedings and Resolutions of the First Congress, 1921 - Taber, Mike (Historical Materialism Book Series, 2025)
The 1921 founding congress in Moscow of the Red International of Labour Unions was a historic event. That gathering set out to create an international revolutionary trade-union organisation embracing millions of workers, and it brought together a wide variety of forces within the world labour movement. Lively and at times acrimonious debates occurred at the congress with syndicalist and other currents over the purpose and tasks of trade unions, the nature of class-struggle unionism, and union strategy and tactics. The congress proceedings, published here in a richly annotated edition, are part of a multi-volume series on the Communist International in Lenin's time. See Less